Perbandingan Modal Ventura Konvensional dan Syariah : Studi Literatur Model Pembiayaan Startup dan UMKM di Provinsi Sumatera Barat - Dewi Mahrani Rangkuty; Alfian Zulmi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
Venture capital is one of the alternative sources of financing for beginner entrepreneurs (startups) and Micro Small and Medium Enterprises (MSMEs). Sharia venture capital is a model of venture capital with the application of Sharia principles in its financing activities. The existence of Sharia venture capital will support the growth of SMEs and startups, especially in West Sumatera. The paper uses a literature study on the venture capital model and the Sharia venture capital model to see a more precise financing model for startup and MSME growth in West Sumatera. Reviews of the study of literature show that, by applying Shariah principles in accordance with the principles of living in society and to support the vision of RPJMD West Sumatra province, the Sharia venture capital model is more appropriate to apply to the startup business and SMEs in West Sumatera. The existence of a Sharia venture capital company became very urgent to be realized immediately. If necessary, sharia venture capital companies can be established in every Regency/city in West Sumatera. The Government should also pay attention to the socialization of Sharia venture capital and also venture capital fund so that the Sharia venture capital that was established can run as the purpose of establishment